THE USE OF ENGLISH SONG LYRICS TO IMPROVE EFL LEARNERS’ PRONUNCIATION MASTERY THROUGH THE SPOTIFY APPLICATION IN UNIVERSITAS PGRI SEMARANG - Calvin Prema Putra; Arso Setiyaji; Festi Himatu K (STKIP Subang, 2024)
This research is based on a study that looks at how far English song lyrics on Spotify can help the 4th semester English education students improve their pronunciation. This study aims to determine the following: 1 To find out the EFL learners’ pronunciation mastery taught before using English song lyrics on Spotify 2 To find out the EFL learners’ pronunciation mastery taught after using English song lyrics on Spotify 3 To know the significant difference between EFL learners’ pronunciation mastery taught before and after taught using English song lyrics on Spotify. This study uses a pre-experimental design. Pre-experimental is an experimental study using one group. The two data that are compared come from student scores before and after being given treatment. In this study, the form of treatment that will be measured for its effectiveness is pronunciation learning using English songs on Spotify. The benchmark or student ability that will be measured is the students’ pronunciation ability through pre-test and post-test. The research design carried out in this study was: 1) Providing a pre-test to the sample to measure pronunciation ability 2) Providing treatment by listening to the song Avalanche by Bring Me The Horizon on Spotify 3) Providing a post-test to the sample to measure pronunciation ability after the treatment. The alternative hypotheses (Ha) in this research was also accepted due to the t-count was higher than t-table with the t-count is 10.299 and the t-table is 1.740. The pre-test mean is 57,1 and the post-test mean is 68,9. It means that there is a significant difference between pronunciation ability before and after being taught by listening to English songs on Spotify.